(untitled) (The Himalayan Geographers, 2025)
The contribution of ecotourism to the sustainable development in Taudaha is the main aim of this study. It is a tiny wetland in a Kathmandu suburb that is significant both culturally and ecologically. In order to assess the economic, ecological, and social effects of ecotourism, the study used a mixed-methods approach that includes surveys, interviews, focus group discussions, and field observations. The findings support a number of Sustainable Development Goals (SDGs) by demonstrating that ecotourism plays a vital part in the local livelihoods, infrastructural development, and environmental awareness. The biodiversity of Taudaha, especially the wetland bird species, is a major drawback to its ecotourism promotion. Similarly, the issues of poor waste management, less community participation, and commercialization risks endure, challenging the area. Therefore, the research proposed co-operation among stakeholders and community-based methods as ways to guarantee equal sharing of benefits and protection of the ecology and environment. Thus, uncovering the potential of ecotourism as a model for integrated development.